Eye lens dose monitoring in the UK nuclear industry using active personal dosemeters. (31st August 2018) - McWhan, A; Dobrzynska, W
Abstract: The reduction of the dose limit for eye lens from 150 to 20 mSv yr −1 must be implemented by EU member states by February 2018. Consequently, there is a requirement for all employers engaged with work with ionising radiation to have appropriate monitoring arrangements in place by this date to demonstrate that they can meet this new limit for all workers. Eye lens dose is conventionally monitored by specific dosemeters worn near the eye. However, it is usually impractical for these dosemeters to be worn at all times in the workplace which can lead to problems accounting for any periods of work when an eye lens dosemeter has not been worn. The Berkeley Approved Dosimetry Service provides a monitoring service for 22 nuclear sites in the UK using active personal dosemeters (APDs) for measuring H p (10) and H p (0.07). TLDs for extremity and eye are also issued as appropriate for the working conditions. An analysis of the data from 2007 to 2016 concludes that the values for H p (0.07) as monitored indirectly by APDs worn on the trunk are comparable to the values assessed by specific H p (3) eye TLDs. This paper sets out evidence that compliance with the 20 mSv dose limit for the eye lens can be demonstrated using routine issue APDs although specific eye TLDs may still be required to meet international guidance for non-uniform workplace fields. This evidence supports the recent statement from International Radiation Protection Association that 'for the nuclear industry and other non-medical sectors the use of a whole body dosimeter is considered likely to be sufficient for the majority of workers'.